FT-IR PROFILE SCREENING OF BIOACTIVE CHEMICAL COMPONENTS IN AQUEOUS EXTRACT OF ABRUS PRECATORIUS LINN PLANT LEAF - GAWADE, BHIMRAJ (Innovare Journal of Sciences, 2020)
Objective: The FT-IR profile screening is aimed to focus on the bioactive chemical components analysis of aqueous extract of Abrus precatorius Linn plant leafs. Methods: The profile screening for the bioactive chemical components analysis was performed with standard methods by using FT-IR spectral technique. Results: The aqueous extract of the leaf were screened for the various bioactive functional chemical components. The spectrum of FT-IR showed the presence different functional groups of chemical constituents such as alcohols, phenols, carboxylic acids, amide, aldehydes, ketones, alkanes, alkenes, aromatics, esters, ethers, aliphatic amines, aromatic amines, peptides, nitro compounds, sulphone, phosphonate, phosphoramide, phosphonic acid, phosphine, silane, amine oxides, aromatic substituted compounds, nitroso, sulphate ester and alkyl halides compounds, which showed 27 major characteristic bands of bioactive chemical components. Conclusion: The results confirm the fact that leaf of Abrus precatorius Linn plant possesses different bioactive functional chemical components and generated the FT-IR spectrum profile for the medicinally important plant.